Integración interdisciplinaria en la educación: contribuciones desde investigación educativa, danza folclórica y enseñanza de la física – un compendio (2026)
The teaching of natural sciences, particularly physics, faces challenges arising from the technological advances of the digital revolution, which demands a rethinking of pedagogical paradigms. In response to the formation of a society for the 21st century, the STEM approach (Science, Technology, Engineering, Mathematics) emerges at the beginning of the 21st century, later evolving toward integrations with the arts, humanities, and related fields. This perspective invites us to conceive scientific education from multiple branches: rigorous research, the recognition of ancestral knowledge, and pedagogical innovation. In this context, the training of graduates in natural sciences with an emphasis on physics is oriented toward strengthening interdisciplinary research, capable of addressing complex educational problems. By integrating dimensions such as cultural preservation through folk dance, ecological and biodiversity perspectives from entomology, and reflective methodologies like Lesson Study or Challenge-Based Learning in STEM, the teacher broadens their perspective for meaningful teaching. The present thesis by compendium of articles contributes to this transformation, relating investigations with SOCOLEN (Colombian Society of Entomology), works on folk dance with Ancestros, contributions in natural sciences, and the project presented at the 4th World Conference on Physics Education, with the aim of evidencing an adaptive and culturally situated teaching practice